Development of Calculus Teaching Materials through Problem-Based Learning Model and Scientific Approach - Sufri Sufri; Feri Tiona Pasaribu (Budapest International Research and Critics University, 2022)
This research is based on the relatively low literacy or problem solving ability and creative thinking level of students towards the teaching material for the